SUNDANESE AESTHETICS IN DARSO’S VIDEO CLIP DULANG KURING 2 - Lingga Agung; Moh Isa Pramana Koesoemadinata (Balong International Journal of Design, 2018)
Abstract This paper aims to see how the aesthetics in the video clip Dulang Kuring 2 which was popularized by Alm.Darso. We used qualitative method as a method in collecting related data and to analyze video clip DulangKuring 2, we use Homi K. Bhabha Post-Coloniam theory about mimicry, hybridity, and “the third space”. The analysis focuses on Darso, the location (landscape), and the setting-property in the video clip. From the analysis that has been done, the aesthetics in the music video clip DulangKuring 2 is paradoxical because it mixes the local and global aesthetic codes. While through the Bhabha postcolonial, we find that the place (landscape), and setting-property gradually mimicry then after that we’ll see another step which is a hybridity that produces “the third space”. From the analysis, the video clip DulangKuring 2 is aesthetically very paradoxical yet hybrid because it targets the contemporary Sundanese society.Keywords: Aesthetic, Communication, Darso, Post-colonialism